(untitled) (Eurasian Medical Research Periodical, 2023)
In order to study the prevalence of major dental diseases in children with congenital heart disease compared to healthy children without somatic disease, children were divided into observation and control groups. The blue and white form of congenital heart defect formed the observation group, and a dental examination was performed